"I Would Hate To See Our Good Name Tarnished": Twitter Users Respond to Sexual Assault in Football. Issue 1 (2nd January 2019) - Waterhouse-Watson, Deb
ABSTRACT: Sexual violence in football has been reported and debated across mainstream and social media platforms since it first become "newsworthy" in 2004, when two cases broke involving footballers from the National Rugby League and Australian Football League. Previous feminist research has identified some problematic trends in mainstream media representations of the cases, identifying rape myths and stereotypes that portray women as liars and provide excuses for footballers' behaviour. However, none has yet considered the ways in which social media users engage with the issue of footballers and sexual violence online. This article focuses on tweets (140-character microblogs from social media platform Twitter) about a rape case involving two players from the Hawthorn Football Club, which occurred shortly after the club won its third successive AFL Grand Final. Content analysis will identify major themes and the key preoccupations of social media users in a rape case involving athletes. Through discourse analysis, the article will explore the ways in which these users rely on or challenge gendered stereotypes and misconceptions about rape, and thus the relative prevalence of feminist understandings of sexual violence. It considers the role of sports fandom in the preoccupations of Twitter users about athlete sexual assault, and how prioritising sports fandom intersects with the way the interests of alleged footballer perpetrators and/or alleged female victims are privileged or marginalised. The article thus highlights the possibilities and limitations of social media as a platform for productive communication about athletes and sexual violence.